Risk of cerebrovascular events in 178,962 5-Year survivors of cancer diagnosed aged 15-39 years: The Teenage and Young Adults Cancer Survivors Study (TYACSS). - Bright, C; Hawkins, M; Guha, J; Henson, K; Winter, D; Kelly, J; Feltbower, R; Hall, M; Cutter, D; Edgar, A; Frobisher, C; Reulen, R (American Heart Association, 2017)
Background Survivors of teenage and young adult (TYA) cancer are at risk of cerebrovascular events, but the magnitude of and extent to which this risk varies by cancer type, decade of diagnosis, age at diagnosis and attained age remains uncertain. This is the largest ever cohort study to evaluate the risks of hospitalisation for a cerebrovascular event among long-term survivors of TYA cancer. Methods The population-based Teenage and Young Adult Cancer Survivor Study (N=178,962) was linked to Hospital Episode Statistics data for England to investigate the risks of hospitalisation for a cerebrovascular event among 5-year survivors of cancer diagnosed when aged 15-39 years. Observed numbers of first hospitalisations for cerebrovascular events were compared to that expected from the general population using standardised hospitalisation ratios (SHR) and absolute excess risks (AER) per 10,000 person-years. Cumulative incidence was calculated with death considered a competing risk. Results Overall, 2,782 cancer survivors were hospitalised for a cerebrovascular event—40% higher than expected (SHR=1.4, 95% confidence interval [CI]=1.3-1.4). Survivors of central nervous system (CNS) tumours (SHR=4.6, CI=4.3-5.0), head & neck tumours (SHR=2.6, CI=2.2-3.1) and leukaemia (SHR=2.5, CI=1.9-3.1) were at greatest risk. Males had a significantly higher AER than females (AER=7 versus 3), especially among head & neck tumour survivors (AER=30 versus 11). By age 60, 9%, 6% and 5% of CNS tumour, head & neck tumour, and leukaemia survivors, respectively, had been hospitalised for a cerebrovascular event. Beyond age 60, every year 0.4% of CNS tumour survivors were hospitalised for a cerebral infarction (versus 0.1% expected. Whereas at any age, every year 0.2% of head & neck tumour survivors were hospitalised for a cerebral infarction 7 (versus 0.06% expected). Conclusions Survivors of a CNS tumour, head & neck tumour, and leukaemia are particularly at risk of hospitalisation for a cerebrovascular event. The excess risk of cerebral infarction among CNS tumour survivors increases with attained age. For head & neck tumour survivors this excess risk remains high across all ages. These groups of survivors, and in particular males, should be considered for surveillance of cerebrovascular risk factors and potential pharmacological interventions for cerebral infarction prevention.